Health data linkage research in Australia remains challenging. Issue 4 (7th April 2019) - Palamuthusingam, Dharmenaan; Johnson, David W.; Hawley, Carmel; Pascoe, Elaine; Fahim, Magid
Abstract: Data linkage is a valuable technique for uniting information from multiple sources that relates to the same person, place, family or event. Despite its value, establishing such linkages in Australia remains challenging. Existing policies are a missed opportunity for research and innovation and engender a negative attitude among researchers when considering data linkage as a research means. Greater leadership from the Population Health Research Network and cooperation from data custodians and Human Research Ethics Committees are necessary to access optimally Australia's enormous data potential.